Correlation of Anthropometry Characteristics and Six-Minute Walking Test Distance In Children Aged 7-8 - Martha Kurnia Kusumawardani1 , Ratna Darjanti Haryadi1 , Andriati1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: The six-minute walk test (6MWT) is a useful test for measuring functional capacity and predicting morbidity and mortality. The 6MWT is not widely used in children because the exact reference data are often not known, and the test requires concentration and co-operation from the participants, which is harder to manage in children. The anthropometry characteristic influences the 6MWT distance. Objective: This study aimed to investigate the correlation between anthropometry characteristic and 6MWT distance in children aged 7-9 years old. Methods: This research was an observational analytic study using cross-sectional design that was conducted on August 2013. Weight, height and body mass index were measured according to the Decree of Ministry of Health Republic of Indonesia. The 6MWT was performed according to American Thoracic Society (ATS) in a 15m indoor walkway. The data were analyzed using several tests, including Kolmogorov-Smirnov test for data normality test and Pearson’s correlation test. Results: The average 6 MWT distance in all subjects was 390.45±50.05 meters, with the average 6 MWT distance in subjects aged 7 and 8 were 370.15±45.64 and 410.75±46.47 meters, respectively. Pearson’s correlation test showed a positive correlation between height and 6 MWT in allsubjects, but there was no correlation between height, weight and body mass index with 6 MWT distance in each age group. Conclusion: The anthropometry characteristic was not correlated with the 6MWT distance in children aged 7 and 8 years old.